Media Dakwah di Era MIlenial Tinjauan Tafsir Al-Qur'an dan Hadits: Studi Penggunaan Media Dakwah pada Komunitas Sentra Kajian Pribadi Nabi - Nanik Mujiati; Nila Audini Oktavia (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2023)
This study aims to find out how the use of da’wah media in the community of Sentra Kajian Pribadi Nabi by Ustaz Ainul Yaqin Lc. MA in the millenials, according to the Qur’an and hadiths commentation. Da’wah activity was in the Shohihuddin islamic boarding 2 interpretations of hadith, Prapen, Surabaya. This method of research uses descriptive qualitative research. The result of research that the da’wah media used consisted of four types, including the first, the media auditif was directly to the public. Such as recitation and lecture activities that have become a routine on Friday nights at the Shohihuddin 2 Tafsir Hadith islamic boarding. Second, visual media giving insight into the book of the da’wah material. Usually visual media dan auditif occur at the same time, such as from the chant together. Third, audio-visual media is a blend of visual media with media auditif one of them is through instagram. That instagram account is a community of Sentra Kajian Pribadi Nabi. Fourth, moral media is a way of delivery that is directly shown in the form of real actions. Ustaz Ainul Yaqin not only spoke in da’wah, but also behaved according to the prophet teachings. He once invited the students he mentored in class to pray in congregation in the mushalla that had been provided in the room.